Chapter Vescovi e signori rurali nella regione trentino-tirolese tra XIV e XV secolo - Tomedi, Andrea (Reti Medievali E-Book, 2023)
The essay illustrates the progressive weakening of the figure of the prince-bishop of Trento, feudal lord of most of the holders of castle lordships in the Trentino area. During the fourteenth century and especially the fifteenth century, noble families learned to look to Vienna and Innsbruck and to participate in the Tyrolean diets. With the sole exception of Alexander of Mazovia, the Trentino prince-bishops following Niccolò da Brno were all faithful to the empire and indeed strong supporters of it.